Edukasi Literasi Keuangan bagi Ibu Rumah Tangga di Kelurahan Beji Depok - Nova Alifah; Tiara Argianti Cayadewi; Faathir Al Bidayah (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
Housewives in Beji Depok, play a central role as family cash flow managers but often face financial stress due to commodity price fluctuation and low financial literacy, leading to consumptive debt cycles. This community service program aims to enhance financial capability through intensive training on budget planning, debt snowball management, and emergency fund allocation. The method consists of three stages: coordination and observation; direct delivery of interactive financial protection lectures with specialized question and answer discussion sessions; and evaluation using a post-event satisfaction questionnaire. The outcomes showed a significant increase in financial comprehension and engagement among the 22 participants. The evaluation confirms that structured community training combined with two-way case discussions effectively builds financial resilience, equips families against predatory digital lending, and motivates consistent emergency savings at the grassroots level.